ECTROPION AS A COMPLICATION OF CRANIO-MAXILLO-FACIAL SURGERY - Cristian Ilie Drochioi; Andrada Raluca Doscas; Doriana Agop-Forna; Alexandra Cracana; Otilia Boisteanu (Romanian Society of Oral Rehabilitation, 2018)
Ectropion is an outward turning of the eyelid margin. Patients may experience symptoms due to ocular exposure and inadequate lubrication. The causes of retraction of the lower lid are multifactorial and may include scarring retraction, horizontal lid laxity, middle lamellar inflammation, or facial palsy. Ectropion is classified as congenital or acquired. In maxillofacial surgery, may appear following procedures related to subcilliary incisions, the management of skin cancer and, nevertheless, post parotidectomy. The aim of the treatment is to restore anatomy, function and aesthetics of the patients.